Inhibition of DTYMK significantly restrains the growth of HCC and increases sensitivity to oxaliplatin - Fengze Sun (Nature Publishing Group, 2021)
Abstract Most patients with hepatocellular carcinoma (HCC) are in the middle or advanced stage at the time of diagnosis, and the therapeutic effect is limited. Therefore, this study aimed to verify whether deoxythymidylate kinase (DTYMK) increased in HCC and was an effective therapeutic target in HCC. The findings revealed that the DTYMK level significantly increased and correlated with poor prognosis in HCC. However, nothing else is known, except that DTYMK could catalyze the phosphorylation of deoxythymidine monophosphate (dTMP) to form deoxythymidine diphosphate (dTDP). A number of experiments were performed to study the function of DTYMK in vitro and in vivo to resolve this knowledge gap. The knockdown of DTYMK was found to significantly inhibit the growth of HCC and increase the sensitivity to oxaliplatin, which is commonly used in HCC treatment. Moreover, DTYMK was found to competitively combine with miR-378a-3p to maintain the expression of MAPK activated protein kinase 2 (MAPKAPK2) and thus activate the phospho-heat shock protein 27 (phospho-HSP27)/nuclear factor NF-kappaB (NF-κB) axis, which mediated the drug resistance, proliferation of tumor cells, and infiltration of tumor-associated macrophages by inducing the expression of C-C motif chemokine ligand 5 (CCL5). Thus, this study demonstrated a new mechanism and provided a new insight into the role of mRNA in not only encoding proteins to regulate the process of life but also regulating the expression of other genes and tumor microenvironment through the competing endogenous RNA (ceRNA) mechanism.